A new species of velvet skate, Notoraja sereti n.sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea - White, William T.; Last, Peter R.; Mana, Ralph R. (Zootaxa, 2017)
A new arhynchobatin skate, Notoraja sereti n. sp., is described based on three specimens collected from off Madang (Papua New Guinea) at depths of 800–980 m. This medium-size Notoraja skate shares with other velcro skates from the Western Pacific, N. alisae, N. fijiensis, N. inusitata and N. longiventralis, a ventral surface covering of fine denticles giving the skin a velvety feel. Notoraja sereti differs from all of these species in having a shorter snout (preorbital length 10.1–11.1 vs. 11.5–14.5% TL, prenasal length 8.2–8.9 vs, 9.8–12.1% TL), shorter head (dorsal head length 15.2–16.2 vs. 17.1–19.3% TL, ventral head length 21.6–22.9 vs. 22.9–25.9% TL), fewer pectoral-fin radials (total radials 58–60 vs. 61–74), and fewer vertebrae (predorsal diplospondylous centra 66–71 vs. 72–82, predorsal centra 90–95 vs. 98–107, total centra 126–131 vs. 135–152).